2009
DOI: 10.3758/brm.41.4.1201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tuned parameters on an LSA multiple choice questions answering model

Abstract: This article presents the current state of a work in progress, whose objective is to better understand the effects of factors that significantly influence the performance of latent semantic analysis (LSA). A difficult task, which consisted of answering (French) biology multiple choice questions, was used to test the semantic properties of the truncated singular space and to study the relative influence of the main parameters. A dedicated software was designed to fine-tune the LSA semantic space for the multipl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…More recently, Lifchitz et al (2009) explored the parameter space of LSA (Landauer & Dumais, 1997) to find the optimal dimensionality of their model across various corpora of different sizes. They found that their optimal tuning of lemmatization, stop-word lists, term weighting, pseudodocuments, and normalization of document vectors in LSA allowed their model to outperform seventh-and eighth-grade students on a multiple-choice biology test.…”
Section: Exploring Parameter Space With Hidexmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Lifchitz et al (2009) explored the parameter space of LSA (Landauer & Dumais, 1997) to find the optimal dimensionality of their model across various corpora of different sizes. They found that their optimal tuning of lemmatization, stop-word lists, term weighting, pseudodocuments, and normalization of document vectors in LSA allowed their model to outperform seventh-and eighth-grade students on a multiple-choice biology test.…”
Section: Exploring Parameter Space With Hidexmentioning
confidence: 99%
“…They found that their optimal tuning of lemmatization, stop-word lists, term weighting, pseudodocuments, and normalization of document vectors in LSA allowed their model to outperform seventh-and eighth-grade students on a multiple-choice biology test. Both of these studies (Bullinaria & Levy, 2007;Lifchitz et al, 2009) show how exploring the parameter space of a high-dimensional model can lead to new insights and unexpected optimal-parameter sets.…”
Section: Exploring Parameter Space With Hidexmentioning
confidence: 99%
“…A single set of parameter values were used for each dataset reported in this paper, and these values were estimated arbitrarily. The optimization issues of LSA have been studied in Lifchitz, Jhean-Larose, and Denhière (2009) regarding optimal tuning of lemmatization, stop-word list, term weighting, pseudodocuments, and normalization of document vectors (see also Shaoul & Westbury, 2010). It is also possible to combine multiple models, for example, by regression analysis or AdaBoost (Freund & Schapire, 1997; see also Bishop, 2006), to improve the model performance.…”
Section: Discussionmentioning
confidence: 99%
“…Probabilistic latent semantic analysis is also used to find similarities between small groups of terms. In particular, in [7] the multiple choice questions (MCQ) answering model using probabilistic latent semantic analysis was described. In [8] the use of probabilistic latent semantic analysis for machine learning tasks and text data mining was specified.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%